AKTIVITAS DIGITAL BUDAYA PARTISIPATIF (STUDI ETNOGRAFI VIRTUAL KRITIK TERHADAP PEMERINTAH PADA PENGIKUT AKUN INSTAGRAM JEROMEPOLIN): (STUDI ETNOGRAFI VIRTUAL KRITIK TERHADAP PEMERINTAH PADA PENGIKUT AKUN INSTAGRAM JEROMEPOLIN) - Salsafila, Nanda Delia; Tri Palupi, Merry Fridha; Sadono, Teguh Priyo (Universitas 17 Agustus 1945 Surabaya, 2026)
Social media has undergone a functional shift from a space primarily associated with entertainment to an arena of public discourse that enables citizens to participate in opinion formation and criticism of government policies. In August 2025, Jerome Polin, a young digital influencer widely known for sharing educational content, along with several other influencers, voiced criticism regarding emerging political issues, particularly the size of the Indonesian House of Representatives’ (DPR) budget, which was perceived as disproportionate to legislative performance and the economic conditions faced by the public. This criticism intensified as the public became increasingly aware of various budget allocations, allowances, and facilities granted to members of the DPR that were considered excessive, while at the same time the government encouraged budget efficiency and austerity measures among citizens. This study aims to analyze digital participatory cultural activities in the process of mobilizing criticism against the government among followers of the Instagram account @jeromepolin, specifically in relation to the issue of DPR allowances framed through the public demand narrative “17+8.” Employing a qualitative approach with a virtual ethnography method, the study focuses on observing digital interactions, analyzing uploaded content, and conducting online interviews with active followers of the account. The findings indicate that Jerome Polin’s posts functioned as catalysts for the formation of a participatory virtual public sphere. Audiences were not merely content consumers but also meaning producers through comments, discussions, reposts, and the redistribution of critical narratives. These practices reflect the core characteristics of participatory culture as conceptualized by Henry Jenkins, including low barriers to participation, support for collaboration, and social engagement in the production and circulation of discourse. The mobilization of criticism observed in this context was non-confrontational yet effective in increasing political awareness, particularly among younger generations, while simultaneously reducing apathy toward governmental issues. This study concludes that digital influencers such as Jerome Polin play a significant role in facilitating the cultural mobilization of criticism through participatory practices on social media. In this context, social media functions not only as a channel for individual expression but also as an informal space for political learning that contributes to the strengthening of civic participation and digital democracy in Indonesia.Keywords: Participatory Culture, Influencer, Mobilization of Criticism, Instagram, Virtual Public Sphere